NILAI-NILAI KITAB TARJAMAH SABIL AL-‘ABID ‘ALA JAWHARAH AL-TAWHID PADA MASYARAKAT PESANTREN KETURUNAN JAWA DI SELANGOR - Mohd Balwi, Mohd Taufik Arridzo bin; Sudardi, Bani (IBDA` : Jurnal Kajian Islam dan Budaya, 2017)
Muhammad Salih Ibn ‘Umar Semarang is one of the scholars from Java who lived during the colonialism of Netherlands in 19 th century un- til the early of 20 th century (1820-1903). He wrote a lot of religious books in Pegon Javanese language. One of his books is the book of Tarjamah Sabil al-‘Abid ‘ala Jawharah al-Tawhid . The book elaborates the principles of one God conception in terms of ahlu Sunnah wa al-Jamaah . Although Muhammad Salih bin ‘Umar Semarang has never been in Malay Peninsula, but his books including Tarjamah Sabil al-‘Abid ‘ala Jawharah al-Tawh id has entered Malay Peninsula and been read as well as been learned by the societies of Malay Peninsula especially the descendants of Javanese society. The book gives sufficient and thoughtful knowledge regarding one God conception. The targeted readers and learners of Tarjamah Sabil al-‘Abid ‘ala Jawharah al-Tawhid are the ordinary Islamic community, especially the Javanese descendants. Therefore, this paper discusses some principles elaborated in the book that influence the faith of Javanese descendants who live in Malay Peninsula based on Ahlu al- Sunnah wa al-Jamaah principles.